Early Nishga-European Contact to 1860: A People for "Those Who Talk of the Efficiency of Moral Lectures to Subdue the Obduracy of the Heart" - Patterson, E. Palmer (Anthropologica, 2022)
This article presents a survey of Nishga-European contact to 1860. The Nishga appear in early accounts as an energetic, intelligent people who were in charge of their own affairs. This independent behavior and attitude struck some Europeans as arrogant and aloof. The vigorous adaptive strategy of Nishga chiefs provided a basis for culture change with continuity throughout the nineteenth century, and also characterized their relationships with those segments of European and Euro-Canadian culture with which they came in contact.